Cropping pattern and intensity in the lower belt of Sarpang District, Bhutan (Asian Journal of Agriculture, 2023)
Abstract. Tashi T, Tobgay T, Wangmo T, Kinley R, Gyeltshen S. 2023. Cropping pattern and intensity in the lower belt of Sarpang District, Bhutan. Asian J Agric 7: 1-6. Information on cropping and farming land use is vital for increasing crop production and identifying production gaps, including planning and investment. Increasing cropping intensity through adopting multiple approaches increases crop production rather than pressure on cropland expansion in many countries. In the case of Bhutan, there is a shortage of information on cropping and its intensity in Bhutan. This study presents the status of cropping patterns and cropping intensity at the household level in the Sarpang District using a multistage random sampling technique. Different forms of multiple cropping practices were recorded in the district but were mostly practiced on a small scale and were intermittent. The rice-based cropping pattern was popular in wetlands, while the maize or vegetable-based cropping pattern predominated in dryland. With an average cropping intensity of 112%, the district had a cropping intensity of 97% and 126% for dryland and wetland, respectively. The landholding size revealed a significant inverse relationship with cropping intensity among farmer characteristics. The district's most serious farming problems were a lack of irrigation water and wildlife crop predation. The study recommends a similar study at the national level and developing appropriate intensification of agricultural land use strategy to minimize pressure on cropland expansion in the future. Similarly, agricultural planning and investment merit assessment of crop diversity, crop production resources, cropping intensity gap, and crop mapping.
Keywords: Cropping intensity, cropping pattern, dryland, land use, wetland